2018
DOI: 10.1016/j.actbio.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tunable, 3D-bioprinted hydrogels on human brown adipocyte behavior and metabolic function

Abstract: Obesity and its related health complications cause billions of dollars in healthcare costs annually in the United States, and there are yet to be safe and long-lasting anti-obesity approaches. Using brown adipose tissue (BAT) is a promising approach, as it uses fats for energy expenditure. However, the effect of the microenvironment on human thermogenic brown adipogenesis and how to generate clinically relevant sized and functioning BAT are still unknown. In our current study, we evaluated the effects of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 71 publications
(71 reference statements)
0
46
0
Order By: Relevance
“…The expression of these genes was further enhanced by co-culture of human umbilical vascular endothelial cells (HUVECs). As opposed to the stiff porous scaffold described in Kuss et al, the flexible and porous cryogel method supported the culture of WAT cells with and without other cell types [123,130].…”
Section: Human Vascular 3d Adipose Disease Modelsmentioning
confidence: 90%
See 1 more Smart Citation
“…The expression of these genes was further enhanced by co-culture of human umbilical vascular endothelial cells (HUVECs). As opposed to the stiff porous scaffold described in Kuss et al, the flexible and porous cryogel method supported the culture of WAT cells with and without other cell types [123,130].…”
Section: Human Vascular 3d Adipose Disease Modelsmentioning
confidence: 90%
“…While the majority of 3D adipose tissue models primarily focus on WAT, Kuss et al aimed to engineer a photocrosslinkable HA and gelatin-based 3D BAT model to explore the role of brown adipose depots in obesity and T2DM [123]. The authors used bioprinted photocrosslinkable methacrylate to alter both the porosity and stiffness of their scaffolds based on varying the spacing parameters during printing and exposure to ultraviolet light, respectively.…”
Section: Human Avascular 3d Adipose Disease Modelsmentioning
confidence: 99%
“…Alginate microstrands have also been used for the differentiation of BAs from murine embryonic stem cells and brown preadipocytes (77). Using 3D printed hyaluronic acid/gelatin gels, Kuss et al (78) showed that whereas immortalized human WA progenitors prefer soft gels, immortalized human BA progenitors prefer stiffer gels, suggesting that developments within WA 3D culture methods cannot necessarily be directly translated to BA cultures.…”
Section: Culturing Bas In 3dmentioning
confidence: 99%
“…Additionally, the adipose-derived cells in the 3D spheroids displayed superior brown adipogenesis relative to 2D culture models [28]. Alternative 3D culture methods, including bioprinting, have likewise displayed superior brown adipogenesis relative to 2D systems in vitro [32][33][34]. Several natural and synthetic biomaterials have been used here to support 3D adipogenic constructs in vitro.…”
mentioning
confidence: 99%